Using the Revised Health Care System Distrust Scale to evaluate healthcare distrust among Chinese men in Hong Kong: An analysis from a prostate cancer screening behaviours survey. (14th June 2022) - Choi, Edmond P. H.; Hui, Bryant P. H.; Wan, Eric Y. F.; Kwok, Jojo Y. Y.; Lok, Kris Y. W.; Lee, Jung Jae
Abstract: Information about the level of distrust in healthcare systems is very limited in Chinese populations, and no validated instrument has been developed to measure this distrust. Therefore, to begin addressing this research gap, this study evaluated the psychometric properties of a traditional Chinese version of the Revised Health Care System Distrust Scale and used it to assess the level of distrust in a healthcare system. The study involved a community‐based personal interview survey of individuals in Hong Kong. A total of 340 men were randomly recruited. In addition to the distrust instrument, the two‐item Trust in Physician Scale and the Patient Health Questionnaire‐9 were used. The two‐factor structure of the distrust scale was confirmed. The item‐total correlations corrected for overlap were >0.4 for both the Competence and Values Distrust subscales, confirming the internal construct validity of the scale. The Cronbach's alpha coefficient was 0.77 for both subscales. The scores of both the Competence and Values subscales were moderately negatively correlated with the total score of the Trust in Physician Scale, providing support for convergent validity. Regarding known‐group validity, the scale could differentiate people according to marital status, monthly personal income and severity of depressive symptoms. Moreover, we found that men who had previously undergone prostate cancer screening had higher Values Distrust scores than those who had not. The descriptive analysis showed that only about half of the participants reported that they received high‐quality medical care and that the healthcare system provided excellent medical care, suggesting that more effort is needed to improve the quality of care and people's satisfaction with healthcare in Hong Kong. In summary, the translated traditional Chinese version of the Revised Health Care System Distrust Scale used in this study is a valid and reliable scale for assessing the level of distrust in a healthcare system.